Le tiret de fin de phrase dans Un cœur simple — un stylème flaubertien ? - Sabine Pétillon; André Petitjean (Flaubert: Revue Critique et Génétique)
The focus of this paper is on Flaubert’s use of the dash in sentence-final position in Un cœur simple. Diachronically, a distinction should be kept between a dash marking the beginning of a line of dialogue and a simple dash, which adds and sets a focus on a linguistic segment in the right context. The latter, whose function is far more subjective than the former, appears in the second half of the 19th century. The dash that we study in the context of Flaubert’s tale is a marker of both fracture and continuity. This is evidenced by the fact that it is often used after a comma or a semicolon and it is sometimes followed by such conjunctions as mais, et, and car. As regards syntax, it should be noted that the dash tends to separates two distinct clauses. We found only one occurrence of the dash operating within the same noun phrase: “[…] et resta fidèle sa maitresse — qui cependant n’était pas une personne agréable...” Here, the presence of the dash between the noun and its relative NP-modifier is the hallmark of Flaubert’s modernity. It should be seen as a syntactic hapax.